Incorrect Pricing Impact on Investment and the Capital Structure of Companies with Financial Constraints - Museloo, Khalil Abbasi; Abartavi, Shaker (International Journal of Economics and Financial Issues, 2017)
The present study aimed to explore the impact of mispricing on capital investment and capital structure in companies with financial constraints. Methodology is descriptive-analytic with casual-comparative research type. Due to homogenization of statistical sample during research years, population was limited to companies were accepted in stock exchange before 2009 and attended till the end of 2014. According to entry criterion, 101 companies were selected by elimination method as the sample. Models by Trinugroho and Rinofah (2011) were used to analyze the research variables, and Kaplan and Zingales index was applied to indicate companies with financial constraints. Data collected by descriptive tests, Kolmogorov-Smirnov test and multi-variable regression. Results showed that there is negative and significant relationship between capital investment and cash flow. The impact of mispricing on capital investment in companies with high financial constraints is not more than companies with less financial constraints. There is reverse relationship between mispricing and debt ratio. The impact of mispricing on debt ratio in companies with high financial constraints is not more than companies with less financial constraints. Keywords: Mispricing, Capital Investment, Capital Structure, Companies with Financial Constraints JEL Classifications: C53, C5, E37, E32